The in vitro determination of the inhibition potential of Lagundi( Vitex negundo L.) on the CYP3A4 metabolism of Azithromycin - Olaivar, Justine T.; Rojo, Audrey Lynette O.; Takata, Bianca Kamille M.; Ruamero, Edwin Jr. (Manila : Department of Pharmacy, College of Pharmacy, University of the Philippines Manila, 2019)
CYP450 play a major role in the metabolism and elimination of drugs and other xenobiotics from the body. It is responsible for many drug-drug and drug-food interactions. With this, it is important to also include herbal medications in the study of enzyme effects. With the increasing advancement and consumption of herbal products, there is an increasing threat of unknown metabolic effects to drugs concomitantly used with these products. Lagundi is one of the herbal products that have gained popularity in the past years. Today, there is no extensive study on the effects of lagundi to CYP450 enzymes, specifically CYP3A4. This in vivo interaction study between Azithromycin and Lagundi used rat liver microsomes isolated through calcium aggregation method. The CYP inhibition assay was done in a reaction mixture containing buffer, NADPH, microsomes, and the ketoconazole positive control or lagundi treatments. This was incubated at 37°C. High-Performance Liquid Chromatography (HPLC) was used to analyze the remaining azithromycin in the assay mixtureThe results also showed that even after extraction from the reaction mixture, there was still matrix effects that occurred. This is evidenced by the high percent yield of azithromycin. The different components of the matrix may have caused hydrolysis of azithromycin causing degradation. All the chromatograms showed similarities in peaks and increase in azithromycin. Therefore, it may be concluded that an initial screen of enzyme effects showed no inhibition of lagundi to CYP450. Although, further studies need to be done to strengthen the integrity of the results by eliminating matrix effects.
Thesis (Bachelor of Science in Pharmacy)--University of the Philippines Manila, June 2019
Keywords: Lagundi -- CYP3A4 metabolism -- Azithromycin -- In vitro determination; Herbal medicine -- Drug interactions -- Cytochrome P-450 -- Vitex negundo